Characteristics and Forensic Identification of Blunt Vertebral Artery Injury - LU Mei-gui, ZHANG Geng, WU Xue-mei, et al. (Fayixue Zazhi, 2021)
Blunt vertebral artery injury occurs frequently in forensic practice. However, injuries of the vertebral artery are easily ignored or overlooked because of its relatively deep location. Through literatures review, this paper finds that the manners of blunt vertebral artery injury are varied and one or more injury mechanisms may be involved simultaneously. Patients often undergo immediate or delayed cerebral apoplexy as well as compression and injury of surrounding structures, due to direct injury or secondary aneurysm or dissection, resulting in disability or death. Diseases such as, vertebral atherosclerosis and dysplasia can increase the disability and death risk and the difficulty of forensic identification. In forensic identification, the details of the case should be considered. For cases of suspected vertebral artery injury, in addition to routine examination of intracranial segment, attention should be paid to the examination of extracranial segment. If conditions permit, angiography can be used prior to or during the autopsy to improve the identification efficiency and accuracy of opinions.